Toward a Generalizable Framework of Disturbance Ecology Through Crowdsourced Science - Graham, Emily B.; Averill, Colin; Bond-Lamberty, Ben; Knelman, Joseph E.; Krause, Stefan; Peralta, Ariane L.; Shade, Ashley; Smith, A. Peyton; Cheng, Susan J.; Fanin, Nicolas; Freund, Cathryn; Garcia, Patricia E.; et al. (Frontiers in Ecology and Evolution, 2021)
Disturbances fundamentally alter ecosystem functions, yet predicting their impacts remains a key scientific challenge. While the study of disturbances is ubiquitous across many ecological disciplines, there is no agreed-upon, cross-disciplinary foundation for discussing or quantifying the complexity of disturbances, and no consistent terminology or methodologies exist. This inconsistency presents an increasingly urgent challenge due to accelerating global change and the threat of interacting disturbances that can destabilize ecosystem responses. By harvesting the expertise of an interdisciplinary cohort of contributors spanning 42 institutions across 15 countries, we identified an essential limitation in disturbance ecology: the word ‘disturbance’ is used interchangeably to refer to both the events that cause, and the consequences of, ecological change, despite fundamental distinctions between the two meanings. In response, we developed a generalized framework of ecosystem disturbances to reconcile this limitation, providing a well-defined lexicon for understanding disturbance across perspectives and scales. The framework results from ideas that resonate across multiple scientific disciplines and provides a baseline standard to compare disturbances across fields. This framework can be supplemented by discipline-specific variables to provide maximum benefit to both inter- and intra-disciplinary research. To support future synthesis or meta-analysis of disturbance research, we also encourage researchers to be explicit in how they define disturbance drivers and impacts, recommend minimum reporting standards that studies should detail about the magnitude, duration, and rate of change of driver and response variables of a disturbance, regardless of scale. We discuss the primary factors we considered when developing a baseline framework and propose four future directions to advance our interdisciplinary understanding of disturbances and their social-ecological impacts: integrating across ecological scales, understanding disturbance interactions, establishing baselines and trajectories, and developing process-based models and ecological forecasting initiatives. Our experience through this process motivates us to encourage the wider scientific community to continue to explore new approaches for leveraging Open Science principles in generating creative and multidisciplinary ideas.